2010
DOI: 10.1149/1.3456625
|View full text |Cite
|
Sign up to set email alerts
|

Nafion Hybrid Membranes for Use in Redox Flow Batteries

Abstract: The membrane is the key component of a redox flow system, as it has to avoid cross-contamination of the ions of the active material as well as to permit high proton conductivity. A membrane with drastically reduced cross-contamination ability would overcome the main problem of several redox couples and, in consequence, a wider variety of redox couples would potentially allow redox flow systems with higher energy densities or lower material costs. This work deals with modifications of Nafion membranes to decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…[16] Recently Schulte et al used this approach to decrease vanadium ion transport through Nafion. [49] They modified the synthesis of both Nafion/SiO 2 and Nafion/ORMOSIL membranes by adding ammonia solution during the sol-gel reaction. Presumably this treatment increases the particle size of SiO 2 inside the Nafion channels [49] and the observed V 4+ ion diffusion through their membranes is about half that reported by Xi et al [41] and Teng et al [42] However, modification of Nafion using diethoxydimethylsilane as the precursor for the sol-gel synthesis of SiO 2 with no addition of ammonia yielded the best result.…”
Section: Nafion and Other Fluorocarbon-based Membranesmentioning
confidence: 99%
See 3 more Smart Citations
“…[16] Recently Schulte et al used this approach to decrease vanadium ion transport through Nafion. [49] They modified the synthesis of both Nafion/SiO 2 and Nafion/ORMOSIL membranes by adding ammonia solution during the sol-gel reaction. Presumably this treatment increases the particle size of SiO 2 inside the Nafion channels [49] and the observed V 4+ ion diffusion through their membranes is about half that reported by Xi et al [41] and Teng et al [42] However, modification of Nafion using diethoxydimethylsilane as the precursor for the sol-gel synthesis of SiO 2 with no addition of ammonia yielded the best result.…”
Section: Nafion and Other Fluorocarbon-based Membranesmentioning
confidence: 99%
“…[49] They modified the synthesis of both Nafion/SiO 2 and Nafion/ORMOSIL membranes by adding ammonia solution during the sol-gel reaction. Presumably this treatment increases the particle size of SiO 2 inside the Nafion channels [49] and the observed V 4+ ion diffusion through their membranes is about half that reported by Xi et al [41] and Teng et al [42] However, modification of Nafion using diethoxydimethylsilane as the precursor for the sol-gel synthesis of SiO 2 with no addition of ammonia yielded the best result. This pub-lication does not contain any data related to VRFB performance with the new membranes, but the authors reported that the electrical resistance of the modified membranes was similar to that observed for pure Nafion.…”
Section: Nafion and Other Fluorocarbon-based Membranesmentioning
confidence: 99%
See 2 more Smart Citations
“…The commonly used dopants are nanoparticles of silica [112,113], including those with a modified surface [114,115], and titania [116]. Modification provides an increase in the coulombic efficiency of RFBs compared with the results for Nafion membranes.…”
Section: Membrane Electrolyzersmentioning
confidence: 99%